Emergence of a Viral RNA Polymerase Variant during Gene Copy Number Amplification Promotes Rapid Evolution of Vaccinia Virus - Cone, Kelsey R. (J Virol, 2017)
Viruses are under relentless selective pressure from host immune defenses. To study how poxviruses adapt to innate immune detection pathways, we performed serial vaccinia virus infections in primary human cells. Independent courses of experimental evolution with a recombinant strain lacking E3L revealed several high-frequency point mutations in conserved poxvirus genes, suggesting important roles for essential poxvirus proteins in innate immune subversion. Two distinct mutations were identified in the viral RNA polymerase gene A24R, which seem to act through different mechanisms to increase virus replication. Specifically, a Leu18Phe substitution encoded within A24R conferred fitness trade-offs, including increased activation of the antiviral factor protein kinase R (PKR). Intriguingly, this A24R variant underwent a drastic selective sweep during passaging, despite enhanced PKR activity. We showed that the sweep of this variant could be accelerated by the presence of copy number variation (CNV) at the K3L locus, which in multiple copies strongly reduced PKR activation. Therefore, adaptive cases of CNV can facilitate the accumulation of point mutations separate from the expanded locus. This study reveals how rapid bouts of gene copy number amplification during accrual of distant point mutations can potently facilitate poxvirus adaptation to host defenses. IMPORTANCE Viruses can evolve quickly to defeat host immune functions. For poxviruses, little is known about how multiple adaptive mutations emerge in populations at the same time. In this study, we uncovered a means of vaccinia virus adaptation involving the accumulation of distinct genetic variants within a single population. We identified adaptive point mutations in the viral RNA polymerase gene A24R and, surprisingly, found that one of these mutations activates the nucleic acid sensing factor PKR. We also found that gene copy number variation (CNV) can provide dual benefits to evolving virus populations, including evidence that CNV facilitates the accumulation of a point mutation distant from the expanded locus. Our data suggest that transient CNV can accelerate the fixation of mutations conferring modest benefits, or even fitness trade-offs, and highlight how structural variation might aid poxvirus adaptation through both direct and indirect actions.